Ethnic variations in the provision of biologic therapy for Crohn's disease: a Freedom of Information study. (June 2015) - Farrukh, Affifa; Mayberry, John F
In this study, we investigate whether the provision of biologic therapy for Crohn's disease is equitable across South Asian and English groups in NHS Trusts, which serve areas with significant ethnic variation. Data were requested from 10 NHS Trusts using a Freedom of Information (FOI) approach. Details of numbers of patients by ethnicity treated with infliximab or adalumimab for Crohn's disease between 2010 and 2012 were requested. Using population-based estimates of disease prevalence and Census data on population structure, observed and expected numbers who should have received treatment were calculated. In three Trusts, the number of South Asian patients who received such treatment was significantly less than British/White patients. These were: Pennine Acute Hospitals NHS Trust covering Oldham and North Manchester, Barking, Havering & Redbridge University Hospitals NHS Trust and University Hospitals of Leicester NHS Trust. The study is limited by several factors: The only data available on prevalence in both English and South Asian communities comes from Leicester and was published in 1993. More recent data suggests that the prevalence of Crohn's disease now approaches 150/10 5 compared to the 76/10 5 for English patients which was recorded in Leicester. However, the two subsequent studies on prevalence which were published in 2000 from the North of England and 2010 from Scotland do not provide a breakdown by ethnicity. The data were collected by administrative staff using a variety of approaches to their Trust's data bases and so the techniques used in each Trust are not comparable. In addition, studies from elsewhere suggest that the quality of FOI data is affected by the motivation of staff who collect the data. With the exception of Leicester, there was no quality check on the accuracy of the data. In Leicester, 139 patients were on a register of biologic therapy and this compared with 343 patients reported by the FOI request. However, the proportions of patients by type of treatment and by ethnicity were comparable in the two data sets. This suggests that the data on ethnic differences reported by the FOI study reflects real differences. Clearly, there are South Asian communities where patients with Crohn's disease appear not to receive appropriate treatment in the form of biologics, and the reasons behind this need further consideration and investigation. We need to develop robust methods of monitoring the provision of biologic therapy across ethnic groups and communities. It is unacceptable for there to be a difference based on such grounds.